TRADIÇÃO E MODERNIDADE NA POESIA DE APPARÍCIO SILVA RILLO, DE 1959 A 1983 - Bertussi, Lisana (Organon, 2007)
Analysis of Apparício Hissing Rillo’s poetry, one of the most important and popular regionalism poets from Rio Grande do Sul state, a member of the gauchesca’s literature system, i. e. the one that takes place in the privileged countryside area – the pampa gaucho, where the main character is the farm worker – o peão, and emphasizes the style of the regional language. The aim of the enquiry is to observe the amount of Modernism influence in his literary work since the sul rio-grandense regionalistic movement is not opposed to the national spirit which endorses it. Additionally it’s of our interest the modernism of the language.